Development of Psychological Problems Among Adolescents During School Closures Because of the COVID-19 Lockdown Phase in Italy: A Cross-Sectional Survey - Esposito, Susanna; Giannitto, Nino; Squarcia, Antonella; Neglia, Cosimo; Argentiero, Alberto; Minichetti, Paola; Cotugno, Nicola; Principi, Nicola (Frontiers in Pediatrics, 2021)
Background: Previous studies have shown that during COVID-19 pandemic, mainly due to the imposed lockdown, significant psychological problems had emerged in a significant part of the population, including older children and adolescents. School closure, leading to significant social isolation, was considered one of the most important reasons for pediatric mental health problems. However, how knowledge of COVID-19 related problems, modification of lifestyle and age, gender and severity of COVID-19 pandemic had influenced psychological problems of older children and adolescents has not been detailed. To evaluate these variables, a survey was carried out in Italy. Methods: This cross-sectional survey was carried out by means of an anonymous online questionnaire administered to 2,996 students of secondary and high schools living in Italian Regions with different COVID-19 epidemiology. Results: A total of 2,064 adolescent students (62.8% females; mean age, 15.4 ± 2.1 years), completed and returned the questionnaire. Most of enrolled students showed good knowledge of COVID-19-related problems. School closure was associated with significant modifications of lifestyle and the development of substantial psychological problems in all the study groups, including students living in Regions with lower COVID-19 incidence. However, in some cases, some differences, were evidenced. Sadness was significantly more frequent in females (84%) than males (68.2%; p < 0.001) and in the 14–19-year-old age group than the 11–13-year-old age group (79.2% vs. 70.2%; p < 0.001). Missing the school community was a significantly more common cause of sadness in girls (26.5% vs. 16.8%; p < 0.001), in southern Italy (26.45% vs. 20.2%; p < 0.01) and in the 14–19-year-old group (24.2% vs. 14.7%; p < 0.001). The multivariate regression analysis showed that male gender was a protective factor against negative feelings (p < 0.01), leading to a decrease of 0.63 points in the total negative feelings index. Having a family member or an acquaintance with COVID-19 increased the negative feelings index by 0.1 points (p < 0.05). Conclusions: This study shows that school closures because of the COVID-19 pandemic outbreak was associated with significant lifestyle changes in all the students, regardless of age and gender. Despite some differences in some subgroups, the study confirms that school closure can cause relevant mental health problems in older children and adolescents. This must be considered as a reason for the maintenance of all school activities, although in full compliance with the measures to contain the spread of the pandemic.